The Perception and Contribution of Community Forest on the Welfare of Farmers in Merapi Volcanoâ€™s Slope - Setiaji, Setiaji; Sadono, Ronggo; Hartono, Hartono; Machfoedz, Mochammad Maksum (Universitas Negeri Semarang, 2017)
Pressure on forest resources causes overexploitation, so that forest resources canâ€™t provide optimal benefits. High demands for timber have created opportunity for the development of community forests in Indonesia. The opportunity has been used relatively well by community forest farmers, such as in Cangkringan Sub-District, Sleman Regency. This study was aimed to learn the economic condition of community forest farmers by calculating income balance, expense, welfare, and perception of community forest farmer family. The data of this study was collected using purposive sampling method, with a total of 60 respondents. Secondary data was collected from related government agencies. The research result showed that most community forests useagroforestry system.Sengon, which is the main community of community forest, serves community savings, which is knownas â€œtebangbutuhâ€ system. 51% respondents agreed to the perception of the importance of community forest.Comprehensive calculation produced positive value, which is bigger than 100% for total percentage of income on expense. Using Sajogyoâ€™s line of poverty, over Â¾ (three fourth) of community forest farmer respondents were above the line of poverty or were able to meet their minimum primary needs.Â